DWARF27 and CAROTENOID CLEAVAGE DIOXYGENASE 7 genes regulate release, germination and growth of gemma in Marchantia polymorpha - Jibran, Rubina; Tahir, Jibran; Andre, Christelle M.; Janssen, Bart J.; Drummond, Revel S. M.; Albert, Nick W.; Zhou, Yanfei; Davies, Kevin M.; Snowden, Kimberley C. (Frontiers in Plant Science, 2024)
Strigolactones (SLs), a class of carotenoid-derived hormones, play a crucial role in flowering plants by regulating underground communication with symbiotic arbuscular mycorrhizal fungi (AM) and controlling shoot and root architecture. While the functions of core SL genes have been characterized in many plants, their roles in non-tracheophyte plants like liverworts require further investigation. In this study, we employed the model liverwort species Marchantia polymorpha, which lacks detectable SL production and orthologs of key SL biosynthetic genes, including CAROTENOID CLEAVAGE DIOXYGENASE 8 (CCD8) and MORE AXILLARY GROWTH 1 (MAX1). However, it retains some SL pathway components, including DWARF27 (D27) and CCD7. To help elucidate the function of these remaining components in M. polymorpha, knockout mutants were generated for MpD27-1, MpD27-2 and MpCCD7. Phenotypic comparisons of these mutants with the wild-type control revealed a novel role for these genes in regulating the release of gemmae from the gemma cup and the germination and growth of gemmae in the dark. Mpd27-1, Mpd27-2, and Mpccd7 mutants showed lower transcript abundance of genes involved in photosynthesis, such as EARLY LIGHT INDUCED (ELI), and stress responses such as LATE EMBRYOGENESIS ABUNDANT (LEA) but exhibited higher transcript levels of ETHYLENE RESPONSE FACTORS (ERFs) and SL and carotenoid related genes, such as TERPENE SYNTHASE (TS), CCD7 and LECITHIN-RETINAL ACYL TRANSFERASE (LRAT). Furthermore, the mutants of M. polymorpha in the SL pathway exhibited increased contents of carotenoid. This unveils a previously unrecognized role for MpD27-1, MpD27-2 and MpCCD7 in controlling release, germination, and growth of gemmae in response to varying light conditions. These discoveries enhance our comprehension of the regulatory functions of SL biosynthesis genes in non-flowering plants.